Functional inhibition related to structure of a highly potent insulin-specific CD8 T cell clone using altered peptide ligands - Petrich de Marquesini, Liliana G (WILEY-VCH Verlag, 2008)
Insulin-reactive CD8 T cells are amongst the earliest islet-infiltrating CD8 T cells in NOD mice. Cloned insulin B15–23-reactive cells (designated G9C8), restricted by H-2K(d), are highly diabetogenic. We used altered peptide ligands (APL) substituted at TCR contact sites, positions (p)6 and 8, to investigate G9C8 T cell function and correlated this with structure. Cytotoxicity and IFN-γ production assays revealed that p6G and p8R could not be replaced by any naturally occurring amino acid without abrogating recognition and functional response by the G9C8 clone. When tested for antagonist activity with APL differing from the native peptide at either of these positions, the peptide variants, G6H and R8L showed the capacity to reduce the agonist response to the native peptide. The antagonist activity in cytotoxicity and IFN-γ production assays can be correlated with conformational changes induced by different structures of the MHC-peptide complexes, shown by molecular modeling. We conclude that p6 and p8 of the insulin B15–23 peptide are very important for TCR stimulation of this clone and no substitutions are tolerated at these positions in the peptide. This is important in considering the therapeutic use of peptides as APL that encompass both CD4 and CD8 epitopes of insulin.